Instruments for assessing health professionals' skills in breaking bad news: protocol for a systematic review of measurement properties. - Gutiérrez-Sánchez, Daniel; García-Gámez, Marina; Leiva-Santos, Juan Pablo; López-Leiva, María Inmaculada (BMJ, 2021)
Introduction: Health professionals are often involved in the process of breaking bad news (BBN), which remains a difficult challenge, as it requires not only theoretical knowledge, but also the development of humanistic, emotional and communication skills. Therefore, optimal BBN assessment is essential. In this regard, sound measurement instruments are needed to evaluate BBN properly in research, teaching and clinical settings. Several instruments have been designed and validated to assess BBN. In this context, choosing the most appropriate instrument for assessing health professionals' skills in BBN is essential. The aims of this systematic review are to: (1) identify all the instruments used for assessing health professionals' skills in BBN; and (2) critically appraise their measurement properties. Methods: A systematic review will be undertaken according to the most up-to-date COnsensus-based Standards for the selection of health status Measurement INstruments' (COSMIN) methodology. The protocol of this systematic review was developed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The search strategy will be performed following the Peer Review of Electronic Search Strategies. The search strategy will be conducted in CINAHL, MEDLINE, Embase, PsycINFO, SciELO and Open Grey. Two review authors will independently appraise the full-text articles according to the COSMIN Risk of Bias checklist. Quality ratings and evidence synthesis will be performed using a modified Grading of Recommendations Assessment, Development and Evaluation approach. Ethics and dissemination: Ethical approval is not necessary for systematic review protocols. The results will be disseminated by publication in a peer-reviewed journal and presented at a relevant conference. Prospero registration number: CRD42020207586
Protocolo de revision sistematica registrada en prospero sobre la comunicacion de malas noticias en el ambito de los cuidados paliativos.
Keywords: Enfermeras y pacientes; Comunicación en enfermería; Adult palliative care; Mental health; Palliative care